Meningkatkan Hasil Belajar Siswa Pada Pelajaran Ilmu Pengetahuan Alam Di Kelas IX-3 Melalui Model Student Team Achievement Division (STAD) Di SMP Negeri 2 Tanjung Morawa Pada Tahun Pelajaran 2019/2020 - Irawati Lebora Hutabarat (Ability: Journal of Education and Social Analysis, 2022)
The objectives of this study were to: Improve student learning outcomes in Natural Sciences lessons in Class IX-3 through the Student Team Achievement Division (STAD) Model at Tanjung Morawa 2 Public Middle School in the 2019/2020 Academic Year. The method used in this research is the Classroom Action Research Method using 2 cycles. The subjects of this study were 32 students of Class IX-3 of SMP Negeri 2 Tanjung Morawa. The technique used to obtain data is using tests, questionnaires and observation. The score range for the test is 1-100. The data analysis technique used is to use the calculation of the number of students' average scores, the percentage of students who complete and the percentage of students who do not complete. The results of this study indicate that there is an increase in learning outcomes by applying the Student Team Achievement Division (STAD) model with the following results: there is an increase in the average student learning outcomes, where in the initial test the average student learning outcomes are 30.31, in cycle I increase to 66.56 then in cycle II it increases again to 75.63 there is an increase in the number of students who pass, where in the initial test the number of students who complete is only 0%, increases to 71.88% in cycle I then increases again to 84.38 % in cycle II, there was a decrease in the number of students who did not complete, where in the initial test the number of students who did not complete reached 100%, in cycle I it became 28.12% then in cycle II it decreased again to 15.62% in other words only 6 students who scored below 70 and the remaining 28 students scored above 70.